Application and Evaluation of The Loop Mediated Isothermal Amplification (LAMP) Method to Detect Wild Boar in Meatball - Wati, Linda; Suhandono, Sony (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The content of meat used in processed meat products such as meatballs must be verified to ensure that the food is halal. Generally, meatballs are made from beef, chicken, and fish. However, some fraudulent practices often occur in the field, which is mixing meatballs with other meats such as wild boar. DNA-based methods can be used because they can sensitively identify the type of meat in meatballs, such as the Loop Mediated Isothermal Amplification (LAMP) method. The LAMP primers designed in this study was tested on DNA isolated from samples of meatballs containing wild boar, chicken, beef, lamb, and rat meat. Positive results were visualized using SYBR green dye, with positive results showing a color change from orange to green. The objective of this study was to design primers capable of detecting wild boar meat DNA in meatballs using simple equipment. The specific wild boar primers successfully detected wild boar meat DNA from meatballs, but the results often showed false positives. Thus, the primers designed in this study are not yet stable and applicable for use in wild boar DNA testing. The combination of the LAMP method with other methods is expected to reduce false positives from the LAMP method.